CLINIC CHARACTERISTICS, DIAGNOSTICS AND THERAPY OF MYOPERICARDITIS AND DIFFUSE MYOCARDITIS - S. R. Mravjan; M. A. Gurevitch (Российский кардиологический журнал, 2003)
In study on a basement of our own research and literature data clinical course of virus myopericarditis was analyzed. Special consideration has been given to characteristics of electrocardiographic indicators, four stages of evolution of cardiographic indicators of illness were emphasized. Increase of hemorrhagic myopericarditis frequency, evidently with virus nature, was noted. Recomendations for treatment in patients suffering from myopericarditis with positive prognosis were given. At the same time, prognosis of diffuse myocarditis remains negative, and indications for its rational treatment determined insufficiently.